GAMBARAN KECEMASAN PADA ANAK SEKOLAH DASAR TERHADAP PERAWATAN GIGI (STUDI LITERATUR) (Jurnal Kesehatan Siliwangi, 2021)
Children’s anxiety was problem that causes children to often delay dental treatment. Besides giving impact for children, children’s anxiety could hinder dentists and sental hygienist performance as well. The aim of this study was to determine the description of anxiety in elementary school children to dental care. The type of research used is literature study. Data was collected by collecting teh literature data and was analyzed by descriptive data analysis method. Literature study result showed that children’s anxiety could be affected by some factors, such as gender, age, visiting experince, and instrumen that get into the mouth. The level of children’s dental anxiety in elementary school showed that many children who feel not anxious with low level of anxiety than children who feel anxious with a high level of anxiety. The dental care that most elementary school children worried was extraction by infiltration (removal with anesthetic injection).